Intergenerational transmission of internalizing behavior: the role of maternal psychopathology, child responsiveness and maternal attachment style insecurity - Reck, Corinna; Nonnenmacher, Nora; Zietlow, Anna-Lena (Psychopathology, 2016)
Maternal depression and anxiety disorders are risk factors for the development of internalizing disorders in offspring. Maternal attachment has been discussed as one factor accounting for transmission. The aim of this study was to investigate child internalizing behavior at preschool age on a symptomatic and behavioral level and possible links to maternal mental health over time and maternal attachment style insecurity in a sample of postpartum depressed and anxious mothers. Sampling and Methods: Child internalizing behavior at preschool age was rated by the Child Behavior Checklist (CBCL), the Caregiver-Teacher Report Form (C-TRF), and during a mother-child free-play situation. We focused on child responsiveness as it has been linked to child internalizing behavior. Maternal attachment style insecurity was tested to mediate the link between maternal mental health (assessed postpartum and at preschool age with the Structured Clinical Interview for DSM-IV Axis-I Disorders, SCID-I) and child internalizing behavior/child responsiveness. Of the overall sample (n = 58), 28 women were diagnosed with postpartum depression and/or anxiety disorders according to DSM-IV, and 30 were healthy controls. Data were collected 3-9 months after delivery and at preschool age (mean = 4.6 years). Results: At preschool age, children of postpartum depressed and anxious mothers were rated significantly higher on child internalizing behavior by mothers, fathers, and additional caregivers compared to the control group. Child internalizing behavior rated by mothers was influenced by current psychiatric symptoms; maternal attachment style insecurity did not mediate this link. During interaction, children in the clinical group displayed significantly less child responsiveness compared to the control group. Maternal attachment style insecurity mediated the relationship between maternal mental health over time and child responsiveness. Conclusions: The results emphasize the need for interventions focusing on mother-child interaction and maternal attachment.
Gesehen am 19.02.2021